A contribution to the problem of atypical polymyositis in children - Hamalová, Jitka; Rozhold, Odolen; Petríková, A; Sprucek, F (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1991)
The diagnostics of polymyositis has frequent difficulties, first af all in atypical forms. These can be presented under different names, which lead clinicians to an erroneous way. For example, "climacteric myopathy" (Kaeser) is considered an endocrinous myopathy, "late onset myopathy" a disease joined with old age (as well as "Werner's disease") or "benign children myopathies" (Walton Natrass). In the last years, a distinctive clinical picture is, due to almost causal therapy by cytostatics and immunosuppressives, worn out and therefore these diseases are called "near states" or "overlap syndrome". In our patients, the correctness of the diagnose was confirmed, apart from electromyographic and histopathological findings, primarily by treatment response and the course of the disease.
Keywords: Child; Follow-Up Studies; dítě; Adult; Male; Muscular Diseases; lidé; dospělí; mužské pohlaví; ženské pohlaví; Female; nemoci svalů; Humans; následné studie